2023
DOI: 10.3390/life14010001
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophyte Infections Worldwide: Increase in Incidence and Associated Antifungal Resistance

Caroline Kruithoff,
Ahmed Gamal,
Thomas S. McCormick
et al.

Abstract: The increase in incidence of superficial fungal infections combined with the emergence of antifungal resistance represents both a global health challenge and a considerable economic burden. Recently, dermatophytes, the main culprit causing superficial fungal infections, have started to exhibit antifungal resistance. This can be observed in some of the most common species such as Trichophyton rubrum and Trichophyton mentagrophytes. Importantly, the new subspecies, known as Trichophyton indotineae, has been repo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 97 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Their abundance and virulence potential fluctuate across different niches and geographic areas, with dermatophytes serving as a prime example, which are more common in tropical regions [16,17]. Effectively, hot, humid climates favor fungal growth, leading to a rise in these infections in tropical and developing countries [18]. However, an experimental study found that neither freezing dermatophytes at −20 • C for 24 h or one week nor exposing them directly to heat at 60 • C for 10, 30, or 90 min was effective in killing dermatophyte conidia [19].…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their abundance and virulence potential fluctuate across different niches and geographic areas, with dermatophytes serving as a prime example, which are more common in tropical regions [16,17]. Effectively, hot, humid climates favor fungal growth, leading to a rise in these infections in tropical and developing countries [18]. However, an experimental study found that neither freezing dermatophytes at −20 • C for 24 h or one week nor exposing them directly to heat at 60 • C for 10, 30, or 90 min was effective in killing dermatophyte conidia [19].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Trichophyton rubrum is the fungus most frequently involved in atypical forms [25][26][27] associated with a strong tendency for dissemination and that are usually refractory to topical and systemic therapy [26]. Moreover, research suggests that Trichophyton rubrum is the primary fungus responsible for chronic dermatophytosis infections [18].…”
Section: Fungal Factorsmentioning
confidence: 99%
“…Fungal infections, particularly those caused by dermatophytes, have become a significant public health concern worldwide [1]. Trichophyton mentagrophytes is a common causative agent of various superficial fungal infections, including athlete's foot, jock itch, and ringworm.…”
Section: Introductionmentioning
confidence: 99%
“…It should also arise in instances of nonresponse to typical first-line topical antifungals (including combination antifungalcorticosteroid topicals) and/or oral antifungals, given the emergence of resistance T indotineae (and other dermatophytes). 11 Additionally, epidemiologic risk factors, such as travel to South Asia 4,7,8 or contact with persons with known or suspected dermatophytosis, should prompt suspicion. 7 Second, clinicians suspecting T indotineae infection should contact their local public health jurisdiction.…”
mentioning
confidence: 99%
“…Suspicion should arise in cases of extensive pruritic dermatophytosis, especially in immunocompetent individuals. It should also arise in instances of nonresponse to typical first-line topical antifungals (including combination antifungal-corticosteroid topicals) and/or oral antifungals, given the emergence of resistance T indotineae (and other dermatophytes) . Additionally, epidemiologic risk factors, such as travel to South Asia or contact with persons with known or suspected dermatophytosis, should prompt suspicion …”
mentioning
confidence: 99%